RESPON PERTUMBUHAN ANAKAN BELANGERAN TERHADAP PENYIRAMAN AIR RAWA GAMBUT, AIR TANDAN KOSONG KELAPA SAWIT, DAN KAPUR DOLOMIT - Basir Achmad; Sulaiman Bakri (Jurnal Hutan Tropis, 2021)
The research aimed to analyze the growth response of belangeran (Shorea balangeran) seedlings on the water of palm oil empty bunches and dolomite lime. The research used a method of a completely randomized design, with the treatments: dolomite lime water, oil palm empty bunch water, and peat swamp water as a control. Based on the ANOVA, the treatment had a very significant effect on the increase of height and diameter of the seedlings. The dolomite lime water increased the seedling height of 9.434 cm, followed by oil palm empty bunches with height increase of 6.800 cm, and peat swamp water/control  with the increase of 5.434 cm. Based on the LSD test, the height increase by dolomite lime water treatment was very significantly different from the height increase by oil palm empty bunches water and the height increase by peat swamp water. The water treatment of empty oil palm bunches increased diameter of 0.156 cm, followed by dolomite lime water with the increase  of 0.147 cm, and peat swamp water with the increase of 0.128 cm. Based on the LSD test, the increase in diameter by the oil palm empty bunches was very significantly different from the diameter increase by the control, but was not significantly different from the increase diameter by the dolomite lime water. It is advisable to mix peat swamp water with dolomite lime with a concentration of 100 grams/200 liters or oil palm empty bunches with a concentration of 5 empty bunches/200 liters of water before using it to water the belangeran seedlings.